ONLINE LEARNING IMPLEMENTATION OF THE INTEGRATIVE CURRICULUM DURING THE COVID-19 PANDEMIC: A DESCRIPTIVE STUDY - Ilman, La Ode; Tobroni; Ishomuddin; Khozin (Journal of Islamic Educational Research, 2021)
This research aims to describe the online learning practice of the integrative curriculum during the COVID-19 pandemic. This research uses a descriptive qualitative approach and data collection is done by interview and documentation. Researcher conducted interviews and collected documents directly from the School Principal and Madrasah Qur’an (MQ) principal. This research finds that online learning of the integrative curriculum is well implemented not only technological support but also because of the direct involvement of teachers, parents, and students simultaneously. The direct involvement shows online learning of the integrative curriculum during the COVID-19 pandemic in the Islamic Boarding School Integral ar-Rohmah Hidayatullah Malang manifested by mapping of time for studying. School curriculum is studied in the morning starting from 07.30 a.m until 11.30 a.m and the tahfizh al-Qur’an curriculum is studied in the morning and afternoon. The morning section started at 05.00 a.m until 06.30 a.m and the afternoon section started from at 03.30 p.m until 05.00 p.m.